2019
DOI: 10.1038/s41539-019-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Lighting the wick in the candle of learning: generating a prediction stimulates curiosity

Abstract: Curiosity stimulates learning. We tested whether curiosity itself can be stimulated—not by extrinsic rewards but by an intrinsic desire to know whether a prediction holds true. Participants performed a numerical-facts learning task in which they had to generate either a prediction or an example before rating their curiosity and seeing the correct answer. More facts received high-curiosity ratings in the prediction condition, which indicates that generating predictions stimulated curiosity. In turn, high curios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
7
36
2
1
Order By: Relevance
“…These results are in line with research that suggests that surprise increases attention to task‐relevant information (Fazio & Marsh, 2009; Stahl & Feigenson, 2019), thereby enhancing learning. In a different experiment (Brod & Breitwieser, 2019), we were able to show that generating a prediction further increases attention to one’s knowledge gap, which leads to increased curiosity for the correct answer. Taken together, the results of our experiments suggest that the effectiveness of generating predictions is at least partially mediated by enhanced attention to the new information.…”
Section: Discussionmentioning
confidence: 74%
“…These results are in line with research that suggests that surprise increases attention to task‐relevant information (Fazio & Marsh, 2009; Stahl & Feigenson, 2019), thereby enhancing learning. In a different experiment (Brod & Breitwieser, 2019), we were able to show that generating a prediction further increases attention to one’s knowledge gap, which leads to increased curiosity for the correct answer. Taken together, the results of our experiments suggest that the effectiveness of generating predictions is at least partially mediated by enhanced attention to the new information.…”
Section: Discussionmentioning
confidence: 74%
“…Alternatively, our IPE findings might be explained by surprise about the content of the information. It has been shown that actively generating predictions about answers to trivia enhances curiosity and learning (Brod & Breitwieser, 2019; Brod, Hasselhorn, & Bunge, 2018) such that the generation of predictions about possible answers leads to larger surprise signals as indexed by pupil dilations (Brod et al., 2018). These results point to an alternative interpretation for our IPE findings to the interpretation drawn from the reward prediction error findings above.…”
Section: Discussionmentioning
confidence: 99%
“…Champagne, Klopfer, & Gunstone, ; Hardy, Jonen, Möller, & Stern, ; Liew & Treagust, ). It is suggested to fulfill various functions, including activating and exposing the learners' prior knowledge, stimulating curiosity for the correct answer (Brod & Breitwieser, ), and – if the prediction is wrong – triggering belief revision because the learners are surprised and realize that there is a flaw in their concept (Brod et al, ). Thus, we believe that our research using well‐controlled and simplistic scenarios in the laboratory could lay a foundation for further research that looks at changes in more complex concepts and their relation with EF skills.…”
Section: Discussionmentioning
confidence: 99%